Pengaruh Penerapan Sistem Informasi Akuntansi Dan Pengetahuan Pengguna Terhadap Efektivitas SISMIOP Pada Badan Pendapatan Daerah Kabupaten Bengkalis - Zulaila Zulaila; Decky Hendarsyah (Politeknik Negeri Bengkalis, 2020)
This research aims to determine whether the application of accounting information systems and user knowledge partially influences the effectiveness of SISMIOP and to find out the application of accounting information systems and user knowledge whether it influences simultaneously the effectiveness of SISMIOP in the Regional Revenue Agency of Bengkalis Regency. Data analysis techniques used are data quality test, classic assumption test, multiple regression test, hypothesis test and coefficient of determination test. Partially, the application of accounting information systems has an effect on the effectiveness of SISMIOP on Bengkalis Regency Regional Revenue Agency with a large influence of 54.7%. Partially user knowledge influences the effectiveness of SISMIOP in Bengkalis Regency Regional Revenue Agency with a large influence of 57.4%. Simultaneously the application of accounting information systems and user knowledge affect the effectiveness of SISMIOP on Bengkalis Regency Regional Revenue Agency with a large influence of 67%.